2020
DOI: 10.1186/s12964-020-00588-9
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous fibroblast growth factor 1 ameliorates diabetes-induced cognitive decline via coordinately regulating PI3K/AKT signaling and PERK signaling

Abstract: Background: Diabetes induces central nervous system damage, leading to cognitive decline. Fibroblast growth factor 1 (FGF1) has dual function of neuroprotection and normalizing hyperglycemia. To date, the precise mechanisms and potential treating strategies of FGF1 for diabetes-induced cognitive decline (DICD) hasn't been fully elucidated. Methods: In this study, db/db mice were used as DICD animal model. We found that diabetes remarkably suppressed FGF1 expression in hippocampus. Thus, exogenous FGF1 had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…CREB is essential for long-term synaptic plasticity changes, and synaptic plasticity mediates the conversion of short-term memory to long-term memory ( Saura and Valero, 2011 ). Ser133 of the N-terminal kinase-inducible domain of CREB is the phosphorylation site of PKA, and p-CREB is the initiating factor for the expression of downstream gene BNDF, which affects synaptic transmission ( Jagasia et al, 2009 ; Wu et al, 2020a ). BDNF promotes the repair and survival of nerve cells, reduces cell apoptosis, and improves learning and memory ( Michalski and Fahnestock, 2003 ; Lu et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CREB is essential for long-term synaptic plasticity changes, and synaptic plasticity mediates the conversion of short-term memory to long-term memory ( Saura and Valero, 2011 ). Ser133 of the N-terminal kinase-inducible domain of CREB is the phosphorylation site of PKA, and p-CREB is the initiating factor for the expression of downstream gene BNDF, which affects synaptic transmission ( Jagasia et al, 2009 ; Wu et al, 2020a ). BDNF promotes the repair and survival of nerve cells, reduces cell apoptosis, and improves learning and memory ( Michalski and Fahnestock, 2003 ; Lu et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The test was performed in a circular pool with a diameter of 120 cm and a height of 40 cm (Jiliang, Shanghai, China). The pool was filled with opaque water colored with milk powder and maintained at 26 ± 1 • C. The training was performed using a hidden circular platform with six blocks of three 60 s trials separated by 20 min inter-block intervals as previously described (Nicholas et al, 2006;Wu et al, 2020a). During the training, the platform remained in the same location relative to the distal cues in the room.…”
Section: Morris Water Maze Testmentioning
confidence: 99%
“…It has been reported that FGF1 ameliorates diabetic nephropathy through exerting its anti‐inflammatory function and suppressing the cellular stress in kidney 15,30 . Moreover, exogenous FGF1 treatment can reverse diabetes‐induced suppression of brain‐derived neurotrophic factor (BDNF) level and elevated neuronal apoptosis, then ameliorate cognitive decline 31 . More importantly, it was previously reported that rFGF1 stimulates liver fat metabolism and effectively ameliorates liver inflammation and damage in ob/ob mice 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes also controls the PI3K/Akt signaling pathway and the PERK signaling pathway. As a result, BDNF production was downregulated, cAMP-response element binding protein (CREB) activity was suppressed, and cognitive performance was decreased [ 92 ].…”
Section: Anti-dcd Effects Of Ebhmmentioning
confidence: 99%